Effect of Refrigerant Change on the Energy Performance of the Heat Pump - Hermanucz, Péter (Journal of Central European Green Innovation, 2022)
To limit the harmful effects of refrigerants and reduce the risks, a hierarchy of legislation has been put in place, ranging from international conventions to standards and nationally approved regulations. These regulations limit the pros and cons of using certain refrigerants and, through them, certain refrigeration solutions: some are being phased out, such as HFC refrigerants used in the normal and deep-freezing range, which pose increased environmental risks but very low health risks. Others are being brought to the fore, albeit with restrictions, such as the so-called natural refrigerants, several of which have direct health risks, such as toxicity, or indirect effects, such as fire and explosion hazards. Many companies in the food industry and related transport and logistics are already using environmentally friendly refrigeration solutions, and their uptake is expected to continue in the future thanks to these regulations. The uptake of these solutions is favoured by their lower specific energy consumption compared to conventional solutions, which means that, despite more complex and dangerous system set-ups, they can be economically and environmentally beneficial.